Compensating elastic faults in a torque-assisted knee exoskeleton: functional evaluation and user perception study - Velasco Guillen, Rodrigo Jose; Bliek, Adna; Font-Llagunes, Josep M.; Vanderborght, Bram; Beckerle, Philipp (Journal of neuroEngineering and rehabilitation, 2024)
Wearable robots are often powered by elastic actuators, which can mimic the intrinsic compliance observed in human joints, contributing to safe and seamless interaction. However, due to their increased complexity, when compared to direct drives, elastic actuators are susceptible to faults, which pose significant challenges, potentially compromising user experience and safety during interaction. In this article, we developed a fault-tolerant control strategy for torque assistance in a knee exoskeleton and investigated user experience during a walking task while emulating faults. We implemented and evaluated the torque control scheme, based on impedance control, for a mechanically adjustable compliance actuator with nonlinear torque-deflection characteristics. Conducted functional evaluation experiments showed that the control strategy is capable of providing support during gait based on a torque profile. A user study was conducted to evaluate the impact of fault severity and compensation on the perception of support, stiffness, comfort, and trust while walking with the exoskeleton. Results from the user study revealed significant differences in participants’ responses when comparing support and stiffness levels without fault compensation. In contrast, no significant differences were found when faults were compensated, indicating that fault tolerance can be achieved in practice. Meanwhile, comfort and trust measurements do not seem to depend directly on torque support levels, pointing to other influencing factors that could be considered in future research.
Created from Fastlane, Scopus look-up
Keywords: Adaptive control; Elastic actuation; Fault tolerance; Human-robot interaction; Impedance control; Wearable robotics